IAEA Safety Standards on Management Systems and Safety Culture - K.D. Persson (Atom Indonesia, 2007)
The IAEA has developed a new set of Safety Standards for applying an integrated Management System for facilities and activities. The objective of the new Safety Standards is to define requirements and provide guidance for establishing, implementing, assessing and continually improving a Management System that integrates safety, health, environmental, security, quality and economic related elements to ensure that safety is properly taken into account in all the activities of an organization. With an integrated approach to management systems it is also necessary to include the aspect of culture, where the organizational culture and safety culture is seen as crucial elements of the successful implementation of this management system and the attainment of all the goals and particularly the safety goals of the organization. The IAEA has developed a set of services aimed at assisting it’s Member States in establishing, implementing, assessing and continually improving an integrated management system.